EVALUATION OF NEW STUDENT ADMISSION POLICY BASED ON ZONATION SYSTEM IN BANDUNG CITY - Hoerudin, Cecep Wahyu (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to evaluate the policy of new student admission based on the zoning system in the city of Bandung using the criteria of effectiveness, efficiency, adequacy, levelling, responsiveness and accuracy. This research is a case study research with a qualitative approach. The implementation of the zoning mechanism in new student admission in the city of Bandung raises various problems in its implementation. Some of the things that are obstacles are still not socialised, constrained by technical factors, insufficient school capacity and the high-quality disparity between schools. For this reason, the zoning system needs to be reviewed so as not to harm students. The results of the policy evaluation of new student admissions based on the zoning system in Bandung city, as a whole, shows that this policy has gone quite well, although there are still problems that must be resolved so that the new student admission in Bandung in the future can run well.Â 